A boundary value problem associated to non-homogeneous operators in Orlicz-Sobolev spaces. Issue 8 (3rd August 2019) - Shokooh, Saeid
ABSTRACT: We apply a three critical points theorem of B. Ricceri to establish the existence of at least three weak solutions for a class of non-homogeneous Neumann problems. Furthermore, by using another theorem of him, we prove that an appropriate oscillating behaviour of the nonlinear term ensures the existence of infinitely many weak solutions. Our analysis is based on recent variational methods for smooth functionals defined on Orlicz-Sobolev spaces.